Aplikasi ESCETE Prima Mobile Credit Union Prima Danarta: Strategi Manajemen Perubahan dan Pengembangan Sumber Daya Manusia yang Kondusif Berlandaskan Ajaran Sosial Gereja - Suhassatya, Gabriel Kristiawan (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
This research paper examines change management strategies and conducive human resource (HR) development in non-profit organizations, specifically at Prima Danarta Credit Union (CU) through the implementation of the ESCETE Prima Mobile application. The purpose of this research is to understand how change management is implemented in non-profit organizations, explore the important role of HR development in supporting change, and evaluate the application of digital technology in financial services through the ESCETE Prima Mobile application. In addition, this research also aims to connect modern management concepts with theological reflection, highlighting the importance of glorifying human dignity in the process of change and technological innovation. The research method used is a descriptive qualitative approach, with critical analysis of change management literature, HR development, as well as theological reflection related to business ethics in the church's social teachings. The results showed that change management at CU Prima Danarta through the ESCETE Prima Mobile application was able to improve the efficiency and quality of financial services for members. This application also helps organizations adapt to technological developments, strengthen HR competencies, and create a work environment that is more responsive to change. Stages of change management such as envisioning, activating, supporting, installing, ensuring, and recognizing were identified as key to the success of the application. This research shows that successful implementation of change management in organizations depends on effective leadership, people development, and the organization's ability to innovate.